INDIVIDUALISM, COLLECTIVISM, AND GOAL ORIENTATION FOR ATHLETES FROM INDIVIDUAL AND TEAM SPORTS - Polina Hadjiyankova; Tatiana Iancheva (Scientific Publishing House. NSA Press, 2021)
In the last years, the issue concerning individualism and collectivism in sport has increasingly attracted researchers' attention. The relation between individualism-collectivism and performance has been surveyed (Cox et al., 1991, Mann, 1980, Wagner, 1995), the stability of teamwork (Kiffin-Petersen & Cordey, 2003, Kirkman, 1996, Kirkman & Shapiro, 2001), team performance (Karsh, 1984, Smith, 1984). This study aimed to examine individualism and collectivism and their relation to goal orientation among athletes with different levels of qualification practicing six different kinds of sport. The research was done among 160 athletes practicing six sports - three (3) team sports and three (3) individual sports. To fulfill the aim of the research, we used: 1. Scale for measuring the horizontal and vertical individualism and collectivism INDCOL of Singelis, Triandism Bhawuk, & Gelfand, 1995; 2. Task and Ego Orientation in Sport Questionnaire - TEOSQ, Duda & Nicholls, adapted for Bulgarian conditions by Domuschieva-Rogleva, 2003. 3. Psychological Collectivism Measure - Jackson et аl., 2006. We established significant differences among competitors practicing individual and team sports and differences depending on the qualification, club affiliation, gender. The influence of individualism and collectivism on goal orientation in sport was revealed.